Multimodal imaging demonstrates concomitant changes in bone and cartilage after destabilisation of the medial meniscus and increased joint laxity. - Moodie, J; Stok, K; Müller, R; Vincent, T; Shefelbine, S (2011)
OBJECTIVE: Alterations in joint mechanics can cause osteoarthritis, which results in degeneration of both cartilage and bone tissue. The objective of this work is to measure changes in the laxity of the mouse knee joint after destabilisation of the medial meniscus (DMM) and to visualise and quantify the resulting three-dimensional changes in the bone and cartilage. METHODS: Skeletally mature C57Bl6 male mice underwent DMM surgery in the right leg. Animals were sacrificed immediately 0 weeks (n=15), 4 weeks (n=11) or 8 weeks (n=12) after surgery. For the 0-week group, the anterior-posterior (AP) and varus-valgus laxity of the DMM limb were compared to the contralateral limb. For 4 and 8-week groups, tibiae were scanned with micro-computed tomography (μCT) to quantify and visualise bone changes and with confocal scanning laser microscopy (CSLM) to measure changes in cartilage. RESULTS: Laxity testing measured an increase in AP range of motion, particularly in the anterior direction. The DMM limbs showed a decrease in epiphyseal trabecular bone at 8 weeks and a decrease in cartilage volume, primarily on the posterior medial plateau, compared to the contralateral limb. Significant bone remodelling was observed at the periphery of the joint and in severe cases, osteolysis extended through the growth plate. CONCLUSION: Multimodal imaging allowed quantifiable 3D assessment of bone and cartilage and indicated extensive changes in the tissues. The increase in AP laxity suggests that DMM surgery redistributes loading posteriorly on the medial plateau, resulting in bone and cartilage loss primarily on the posterior portion of the medial plateau.